Zur Leistung von Adjektiven in Vorstellungstexten von Ärzten – eine Analyse anhand der Profile auf Arztbewertungsportalen - Gabriela Rykalová (Linguistische Treffen in Wrocław)
Introduction texts are a type of text whose establishment goes hand in hand with the development of the Internet and websites. The aim of the texts is to present oneself in a private or professional context. The focus of this article is on a special variant of introductory texts, i.e. introductory texts from medical professionals published on their profiles on the German doctor rating portal jameda.de. The portal is regarded as a media space, which is used, among other things, for the public presentation of doctors. On the basis of the introductory texts taken from the profiles of doctors specialising in orthopaedics and orthopaedics and surgery, an attempt is made to answer the question of the performance potential of adjectives in these texts. When reading the texts, it is noticeable that adjectives occur more frequently in different parts of the texts with different purposes and functions. With this in mind, the focus is on showing which adjectives are used in which parts of the introduction texts and with which functions are used. The examination of the corpus shows that three basic functions can be attributed to adjectives. They are used to qualify certain components of self-presentation objectively or subjectively. In some places in the texts, they also serve to emotionalise. Overall, it can be stated that the adjectives have a persuasive effect in many cases and make an important contribution to creating a positive image of the doctor. The analysis of the linguistic material basis is preceded by a theoretical introduction to the nature of the text type of the imaginative text and its text type variant, which represents the texts of doctors.